Macronutrient and Micronutrient Intake as Determinants of Underweight Among Toddlers in Toddlers at the Molino Community Health Center, North Morowali Regency - Early Masita; Tasnim Tasnim; Islaeli Islaeli (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: The prevalence of underweight in toddlers in the Molino Community Health Center mining area increased sharply from 9.98% (2023) to 15.32% (2024), exceeding the national target of 12% and reflecting a serious nutritional crisis in North Morowali Regency which also increased from 6.41% to 13.24%. This condition differs from the stability of the national prevalence of around 16.29%, indicating a specific problem in the mining area related to the imbalance of macro and micro nutrient intake. This study aims to macronutrient and micronutrient intake as determinants of underweight among toddlers in toddlers at the Molino Community Health Center, North Morowali Regency. Method: This study used a quantitative approach with a case-control matching design of toddlers in the Molino Community Health Center area from April to June. A sample of 186 toddlers (93 underweight, 93 with normal nutrition) was selected from a population of 1,253 children using the Slovin formula and cluster random sampling. Result: The results of the analysis showed that there was an influence of limited access to health services with OR=1.729, while the most dominant factors were the influence of macronutrient intake (OR=4.912; CI 95%: 2.635–9.159) and the influence of micronutrient intake (OR=4.013; CI 95%: 2.179–7.390) on the nutritional status of toddlers. Conclusion: The analysis model shows that the variation in nutritional status is quite good, it is recommended to carry out family-based nutritional interventions, increase education for parents, and strengthen community economic empowerment programs through integrated promotive and preventive services at the Community Health Center.